2021
DOI: 10.7759/cureus.14550
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Fluorescence Imaging for Sentinel Lymph Node Identification in Melanoma Surgery

Abstract: Although less common than other types of skin cancers, melanoma is accountable for the majority of skin cancer-related deaths. The standard management for patients with clinically negative nodes includes a sentinel lymph node (SLN) biopsy, which is commonly performed using a combination of radioactive tracer (Tc-99) and a blue dye (isosulfan or patent blue). There are numerous drawbacks associated with Tc-99 and blue dyes such as elevated costs, logistical challenges, and anaphylactic reactions among others. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…ICG angiography has revolutionized surgeons' ability to assess tissue perfusion in the operating room. First introduced in the 1950s, ICG is a unique tricarbocyanine dye that allows real-time targeted anatomical visualization due to its high level of contrast against the background, innate ability to be taken up in small concentrations, rapid excretion into the bile, ease of use for prospective clinicians and researchers, low toxicity potential, and affordability [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ICG angiography has revolutionized surgeons' ability to assess tissue perfusion in the operating room. First introduced in the 1950s, ICG is a unique tricarbocyanine dye that allows real-time targeted anatomical visualization due to its high level of contrast against the background, innate ability to be taken up in small concentrations, rapid excretion into the bile, ease of use for prospective clinicians and researchers, low toxicity potential, and affordability [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ICG has demonstrated a rapid clearance (half-life of 3-5 minutes) from the body via first-order kinetics in the form of nonconjugated bile [2,5]. ICG also has a very low toxicity profile, with reported cases of 1/40,000 [6,7,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, scientific efforts are now devoted to designing new optical imaging probes that can generate high-contrast and reliably localized SLNs and nodal micrometastases, enabling the real-time tailoring of surgical approaches while reducing the duration of anesthesia time and risk of nerve injury. A study led by Ferri et al has recently highlighted that NIR fluorescence imaging using ICG may be a more effective, safe, less costly, and more convenient alternative for the identification of SNL in melanoma [ 189 ]. The authors presented the case of a 51-year-old patient with melanoma in his upper back, where NIR fluorescence was successfully employed to detect two SLNs in the left axilla.…”
Section: Anatomical Imaging Techniquesmentioning
confidence: 99%
“…They also reported that ICG, a water-soluble tricarbocyanine dye, offers potential advantages for radiotracer-based lymphoscintigraphy including good tissue penetration, an excellent safety profile, and real-time intraoperative imaging capabilities. However, at the moment, NIR fluorescence using ICG is recommended for clinical use only in combination with lymphoscintigraphy for primary CM [ 189 , 190 ]. Nonetheless, other research groups have focused on examining the potential of nanoparticles in NIR imaging for the intraoperative detection and visualization of SLN.…”
Section: Anatomical Imaging Techniquesmentioning
confidence: 99%